Plant Circadian Networks Methods and Protocols - Staiger, Dorothee; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2014)
Plant Circadian Networks: Methods and Protocols provides a collection of protocols to investigate clock-controlled parameters including transcript and small RNA levels, promoter activity using luciferase reporters, protein levels and posttranslational modification, protein-protein interaction, in vivo DNA-protein interaction and RNA-protein interaction, cellular redox state, Ca2+ levels, and innate immune responses. Furthermore, the use of bioinformatics resources is described to evaluate high throughput data sets and to integrate the data into an overarching picture of circadian networks in the cell. Additional chapters focus on seasonal processes like flowering time control, and techniques on trees, moss and algae.   Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls.   Authoritative and practical, Plant Circadian Networks: Methods and Protocols is designed not only for the chronobiology community dealing with circadian biology but also for the plant community in general.
Measurement of Luciferase Rhythms -- Online Period Estimation and Determination of Rhythmicity in Circadian Data, using the BioDare Data Infrastructure -- Global profiling of the circadian transcriptome using microarrays -- ChIP-Seq analysis of histone modifications at the core of the Arabidopsis circadian clock -- Quantitative transcriptome analysis using RNA-seq -- Rapid and parallel quantification of small and large RNA species -- The RIP per case – identification of RNA binding protein targets by RNA immunoprecipitation -- A protocol for visual analysis of alternative splicing in RNA-Seq data using Integrated Genome Browser -- AthaMap web tools for the analysis of transcriptional and post-transcriptional gene expression regulation in Arabidopsis thaliana -- Analysis of mRNA translation states in Arabidopsis over the diurnal cycle by polysome microarray -- Immunoprecipitation-based analysis of protein-protein interactions -- Comparative Phosphoproteomics to Identify Targets of the Clock-Relevant Casein Kinase 1 in C. reinhardtii Flagella -- Pulsed induction of circadian clock genes in Arabidopsis seedlings -- The use of fluorescent proteins to analyze circadian rhythms -- Measuring circadian oscillations of cytosolic-free calcium in Arabidopsis thaliana -- Circadian life without micronutrients: effects of altered micronutrient supply on clock function in Arabidopsis -- Assessing redox state and reactive oxygen species in circadian rhythmicity -- Circadian regulation of plant immunity to pathogens -- Determination of photoperiodic flowering time control in Arabidopsis and barley -- The perennial clock is an essential timer for seasonal growth events and cold hardiness -- Monitoring seasonal bud set, bud burst and cold hardiness in Populus -- Transformation and Measurement of Bioluminescence Rhythms in the Moss Physcomitrella patens -- Modeling and Simulating the Arabidopsis thaliana Circadian Clock Using XPP-AUTO.
Keywords: Plant science; Botany; Plant Sciences